Coronavirus disease (COVID-19) and Africa: Acclaimed home remedies - Orisakwe, Orish E.; Orish, Chinna N.; Nwanafor, Eudora O. (ScienceDirect, 2020)
At last the WHO declared the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) now known as COVID-19 a pandemic. Amidst uncertainty both in the pathophysiology and the management of COVID-19, many African countries in the face of either overstretched or non-existent healthcare infrastructure resorted to home remedies as immediate alternative or first line of action. The present study is a synoptic capture of these home remedies with an attempt to understand the pharmacological basis on which these choices are predicated. Literature was compiled from google, social media, Radio and Television commentaries and news with stringent inclusion and exclusion criteria. Natural spices (turmeric, ginger, garlic etc.) and leaves (neem, paw, guava, etc.) with notable antioxidant and anti-inflammatory properties were found to be beneficial. These home remedies may hold promise in the prophylaxis and cure of COVID-19 infection
Keywords: Public health; Natural products; Home remedies; Covid-19; Viral infection; University of Port Harcourt; ACE-PUTOR; ACE: Public Health and Toxicological Research